2015
DOI: 10.1007/s11104-015-2428-2
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping maintains soil fertility in terms of chemical properties and enzyme activities on a timescale of one decade

Abstract: Background Overyielding (i.e., mixtures of crops yielding higher than expected when compared with monocultures) and increased nutrient acquisition have been found in many intercropping systems. However, there are very few published studies on long-term changes in soil chemical and biological properties in intercropping systems compared to sole cropping. Methods A field experiment was established in 2003 in Gansu province, northwest China. The treatments comprised three intercropping systems (either continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 78 publications
(83 reference statements)
4
59
1
Order By: Relevance
“…In recent years, legumes intercropping, green manure, and goat manure has been widely used in red soil acidity and fertility improvement, which has gradually become a hot spot [38][39][40][41]. Most of the previous studies have shown that legumes intercropping and manure are beneficial for improving soil fertility and increasing yield [42][43][44][45]. In this study, chlorophyll contents, sprouts lengths, biochemical components, and the weight of hundreds 20-Y tea plantation improved with the integrated use of green and goat manure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, legumes intercropping, green manure, and goat manure has been widely used in red soil acidity and fertility improvement, which has gradually become a hot spot [38][39][40][41]. Most of the previous studies have shown that legumes intercropping and manure are beneficial for improving soil fertility and increasing yield [42][43][44][45]. In this study, chlorophyll contents, sprouts lengths, biochemical components, and the weight of hundreds 20-Y tea plantation improved with the integrated use of green and goat manure.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, chlorophyll contents, sprouts lengths, biochemical components, and the weight of hundreds 20-Y tea plantation improved with the integrated use of green and goat manure. These profitable effects may be due to the maintenance and improvements of pH [46][47][48], available nutrients status [40,49], Aluminum detoxification [45,50], stimulation of low molecular weight organic acid [51], and the improvement of microbial activity and community structure [52]. Leguminous green manure has nitrogen fixation ability, plays an important role in the soil nitrogen balance, and can increase the effectiveness of phosphate and some trace elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As they cover an important part of the soil, intercropped plants produce more shade, keep soil humidity and create more buffer microclimatic conditions (Siles et al, 2010). It also improves both physical (porosity) and chemical soil properties (soil pH, enzymes) (Wang et al, 2015). In Parana State in Brasil, coffee was intercropped with the cultivation of legumes, especially Leucaena leucocephala L. (Fabales: Mimosaceae), which significantly increased the soil enzyme activity (urease, arylsulfatase and phosphatase) as well as the Carbon and Nitrogen mineralization rates (Balota & Chaves, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Urease is involved in nitrogen (N) transformation as it helps in producing ammonium, which is the major N source for plant growth (Bachmeier et al ., ). Soil phosphatase is closely related to the transformation of phosphorus (P), which assists soils to catalyse organic P into inorganic P (available to crops) (Liang et al ., ; Wang et al ., ). In addition, catalase is an important oxidoreductase participating in energy conversion, which promotes the decomposition of hydrogen peroxide to water and oxygen, thus reducing the toxic effects on organisms (Brzezinska et al ., ; Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 97%